Attraction and Promotion Strategies in the Development of Muslim-Friendly Tourism in Tangkahan Langkat Ecotourism - Slamet Widodo; Lambok Manurung; Etty Harya Ningsi; Irna Trianur Lubis (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Muslim-friendly tourism has become an important global trend, including in Indonesia, as the growing Muslim travel market increasingly demands destinations that integrate attractive natural and cultural resources with halal-compliant facilities and effective promotion to ensure spiritual comfort and positive travel experiences. This study analyzes the influence of tourist attraction and tourism promotion on tourist in the context of Muslim-friendly tourism development. The study used a quantitative approach with 100 foreign tourist respondents selected through non-probability sampling (accidental sampling). Data were collected through questionnaires, observations, and documentation, then analysed using multiple linear regression. The results show that tourist attraction and tourism promotion have a positive and significant effect on tourist visits, both partially and simultaneously. The Adjusted R Square value of 0.805 indicates that 80.5% of the variation in tourist visits can be explained by the two variables, while 19.5% is influenced by other factors outside the model. The findings confirm the need to strengthen local culture-based attractions and the creative economy, as well as optimise digital promotion through social media to enhance the image of the destination and tourist visits.